POLITIK IDENTITAS DAN IMPLIKASINYA TERHADAP INTEGRASI BANGSA DAN PENATAAN PEMERINTAHAN DAERAH - Hadi, Krishno (Jurnal Bestari, 2008)
The general indication of the local political dynamic relates to the existence of national political entity. In other words, all politics is local. In our context, there are two fundamental considerations why this local politics are important. First, the construction of our national political system seems to be weak compared to that of local political system established many years or hundred years ago. Second, the reality set in local issues, such as race and ethnicity tend to be permanent, so that we need to manage the local issue and use it the energy of politics to enhance the political dynamics and government of Indonesia. In this case. we do not need to cover the local issue. Decentralization and region autonomy provides the people a space to arrange their own government based on their wants and characteristics. This topic becomes the basic reason of politics identity.